Application of Interactive Learning Media Akhlak in Improving Student Learning Outcomes in Class VIII MTS DDI Tapandullu Kab. Mamuju - Ahmad R; Hamdanah; Abdul Khalik; St. Aminah; Saepudin (Universitas Muhammadiyah Palu, 2024)
The research results obtained are: (1) Student activity in learning shows an increase from cycle to cycle. In the first cycle the student activity showed a score of 74.7%, then in the second cycle it increased to 84.1%, and the third cycle increased again to 92%, (2) The students' responses to learning with this Interactive Learning Media, they stated that it was very fun, not bored and easy to understand. (3) Student learning outcomes have increased which is reflected in the percentage gain. The percentage score in the first cycle was 36.7% with 11 students' completeness, in the second cycle it increased to 80% with 24 students' completeness, then in the third cycle it increased again to 90% with 27 students' completeness. Thus it can be concluded that through the application of interactive learning media it can improve the learning outcomes of the moral creed of class VIII MTS DDI Tapandullu.